Institutions, Culture, and the Tropical Development Gap: The Agro-Climatic Origins of Social Norms about Thrift and Sharing. Issue 3 (3rd July 2019) - Poirine, Bernard; Dropsy, Vincent
Abstract: The development gap between countries in tropical and temperate zones has been attributed to a variety of factors. Using data from the World Values Survey, we find that social norms about thrift, as opposed to sharing, vary with the length of the winter season. We also show that this cultural dimension "thrift versus sharing" and institutional quality both have an independent effect on contemporary economic outcomes. This suggests that the tropical development gap might be the consequence of deep-rooted effects of pre-industrial agro-climatic conditions on both the quality of institutions and social norms about thrift versus sharing that fostered development in the industrial era.